2016
DOI: 10.1016/j.drugpo.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

The transparency paradox. Building trust, resolving disputes and optimising logistics on conventional and online drugs markets

Abstract: On virtual drug markets practices of building trust, conflict resolution and logistics is constantly evolving. They offer improved security solutions on the one hand while on the other hand scamming and fraud seem to be widely used on both online and conventional drug markets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
114
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(123 citation statements)
references
References 24 publications
1
114
0
3
Order By: Relevance
“…One of the least understood aspects of cryptomarket-related harms is their relationship to systemic drug violence. Quantitative and qualitative research on this topic is limited, but also significant, showing reduced perceptions, expectations, and experiences of violence for people who buy and sell illicit drugs online in comparison to those involved in conventional, offline drug trading [3][4][5]. This is consistent with earlier conceptual research which suggests that cryptomarkets offer an important avenue whereby many of the harms associated with illicit drug distribution, including systemic violence, may be minimised [6,7].…”
supporting
confidence: 71%
See 1 more Smart Citation
“…One of the least understood aspects of cryptomarket-related harms is their relationship to systemic drug violence. Quantitative and qualitative research on this topic is limited, but also significant, showing reduced perceptions, expectations, and experiences of violence for people who buy and sell illicit drugs online in comparison to those involved in conventional, offline drug trading [3][4][5]. This is consistent with earlier conceptual research which suggests that cryptomarkets offer an important avenue whereby many of the harms associated with illicit drug distribution, including systemic violence, may be minimised [6,7].…”
supporting
confidence: 71%
“…A recent study by Vrolijk et al [4] showed that test results provided on websites about ecstasy tablet composition often do not correspond to what is actually in the tablet, and 15% of the provided test results could even be considered dangerous to the consumer. This was confirmed by a recent study of the composition of new psychoactive substances purchased on Google-indexed webshops [5].…”
Section: Focus On Cryptomarkets and Online Reviews Too Narrow To Debamentioning
confidence: 99%
“…positive, negative or neutral). These features show how important are the trust and the reputation among a cryptomarket community [12]. As a cryptomarket grows, the number of bitcoins held in escrow may become huge and constitute a target for hackers or even administrators themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Lists of products and services offered by sellers are organised into categories and subcategories. Sellers -and their products -are evaluated according to the feedback left by their previous customers, trust and reputation being central components of the trade on cryptomarkets [3]. Unlike conventional sales sites, however, cryptomarkets facilitate exchanges in a context where the anonymity of administrators and participants is protected thanks to the combination of encryption features.…”
Section: Introductionmentioning
confidence: 99%